Examining the Relationship between Infection Control Practices and ESBL Bacterial Carriage in Healthcare Workers - Ayunisih, Lintang Sekar; Krisniawati, Nia; Wicaksono, Madya Ardi; Hestiyani, Rani Afifah Nur; Widhi, Anriani Puspita Karunia Ning (Fakultas Kedokteran Universitas Brawijaya, 2024)
The Enterobacteriaceae family widely produces Extended Spectrum Beta-Lactamase (ESBL), and infection by ESBL-producing bacteria can significantly increase morbidity, complicate therapeutic difficulties, escalating healthcare costs, and increase mortality rates. Transmission of these bacteria within the hospital environment may lead to the prevalence of ESBL-producing bacterial carriers among healthcare workers. Health workers' infection prevention and control (IPC) behavior plays a role in transmitting these pathogenic bacteria. This study aimed to determine the relationship between IPC behavior and the incidence of ESBL-producing bacterial carriers in health workers at Banjarnegara Islamic Hospital. This research used an observational analytic approach with a cross-sectional method. The sampling technique involved purposive sampling, resulting in a total sample of 61 people. Data were obtained by completing an IPC behavior questionnaire and collecting rectal swab samples cultured on CHROM ESBL Agar media. Statistical analysis was done using the Mann-Whitney test. The research identified a prevalence of 13.1% (8/61) ESBL-producing bacterial carriers among health workers at Banjarnegara Islamic Hospital. However, based on statistical analysis, the p-value was 0.664, leading to the rejection of the hypothesis (accepted if p-value <0.05). In conclusion, there is no significant relationship between IPC behavior and the incidence of ESBL-producing bacterial carriers in health workers at Banjarnegara Islamic Hospital.